Um Enigma e sua Esfinge - Cunha, Paulo Ribeiro Rodrigues da [UNESP] (My University, 2014)
This essay is targeted to ransom some aspects in General Miguel Costas´political trajectory; and also, the controversial debate concerning the Coluna Prestes. Here the attention is focused on his (the General’s) lack of knowledge even in the university matters, as also about the very Policia Militar (Military Police) institution. Considering a hypothesis, this came to happen on account of too few study material on the institution originated by the scholars efforts, but it happened also because the own Policia Militar were afraid that him would be sight like a leftish policeman.

Este artigo objetiva o resgate alguns aspectos da trajetória política do General Miguel Costa e o debate sobre a Coluna Prestes, chamando atenção sobre seu desconhecimento tanto na universidade bem como na própria instituição polícia militar de São Paulo. Por hipótese, isto se deve aos poucos estudos sobre a instituição entre os acadêmicos, mas também pelo receio da própria PM Paulista no sentido de apreendê-lo como um policial de esquerda.
Keywords: Coluna Prestes; Miguel Costa; Tenentismo